Design of a Mobile Application for the Monitoring and Control Exercised by Children on their Smartphones - Lida Violeta Asencios-Trujillo (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This research work will cover the creation of a mobile application to help parents with the monitoring and control that they will exercise over their children on their smartphones. Many times, children use the phone excessively, and parents cannot control it. There are many mobile apps that help with parental control and that way parents can have a control over their children, but all those parental control apps have a paid amount. What we want to do in this research work is to create a parental control application that helps parents by giving them benefits in its use for free and thus users would not have to pay any amount of money to have access to all their functions.